Kokkuvõte kliinilisest auditist „Täiskasvanute kõrgvererõhktõve käsitlus esmatasandil“ - Rätsep, Anneli; Kalda, Ruth; Martinson, Katrin; Asi, Signe; Gross, Lilli; Poom, Katrin; Lõmps, Pille; Unukainen, Tiina; Joona, Sirli (Eesti Arst, 2018)
Eesti Arst 2018; 97(4):185–190